Membuat Dokumen Tata Laksana Manajemen Insiden Berdasarkan Framework IT Infrastructure Library V.3 - Khurotul Aeni; Bambang Soedijono W.A; Henderi - STMIK AMIKOM Yogyakarta (Universitas Bina Sarana Informatika, 2016)
Abstract -Tata like IT incident management needs to be done as a guide, and internal controls to ensure service levels especially on academic information system (AIS) meets the standards or to follow best practices. For documents that need to be made governance of incident management for the handling of incidents can run well and according to expectations of the organization, and ultimately the success of IT objectives (IT Goal) and the ultimate goal of business processes (Business Goal). The development of academic information systems at the University of Civilizations basically been done, but not optimally. Application of SOP (Standard Operating Procedure) and SLA (Service Level Agreement) on academic information system services is still conventional, not optimal in a structured incident handling. For making a documentary of governance should be evaluated first, this was done to assess the extent to which each IT process in academic information systems function in accordance with the purpose of application development, especially for the incident handling process. Pengukurann maturity level is used to determine and evaluate the current state of the academic information system (SIA) today. This study is adapted from the IT Infrastructure Library framework which refers to the process of incident management. The study provides some recommendations for improvement related to the areas of incident management. The measurement results using a maturity level that existed at COBIT 4.1, shows the maturity level is currently at level 2 (Repeatable but Intuitive), and through the use of the Goal Question Metric, where there are four areas that need to be improved to create a document governance management, namely: helpdesk application, the application of SOP (Standard Operating Procedure), the application SLA (Service Level Agreement), and the application of servicedesk team.Keywords: Incident Management, IT Infrastructure Library, Procedures Abstrak –Tata laksana manajemen insiden TI perlu dilakukan sebagai panduan dan pengendalian internal untuk memastikan tingkat layanan khususnya pada sistem informasi akademik (SIA) telah memenuhi standar atau mengikuti praktek-praktek terbaik. Untuk itu perlu dibuat dokumen tata laksana manajemen insiden agar penanganan insiden dapat berjalan dengan baik dan sesuai harapan organisasi, serta pada akhirnya menyukseskan tujuan TI (IT Goal) dan tujuan akhir dari bisnis proses (Business Goal). Perkembangan sistem informasi akademik di Universitas Peradaban pada dasarnya sudah dilakukan, namun belum secara optimal. Penerapan SOP (Standard Operating Procedure) dan SLA (Service Level Agreement) pada layanan sistem informasi akademik masih bersifat konvensional, belum optimalnya penanganan insiden secara terstruktur. Untuk pembuatan sebuah dokumen tata laksana perlu dilakukan evaluasi terlebih dahulu, hal ini dilakukan untuk menilai sejauh mana setiap proses TI pada sistem informasi akademik berfungsi sesuai dengan tujuan pengembangan aplikasi terutama untuk proses penanganan insiden. Pengukurann maturity level digunakan untuk mengetahui serta mengevaluasi kondisi saat ini pada sistem informasi akademik (SIA) saat ini. Penelitian ini diadaptasi dari framework IT Infrastructure Library yang mengacu pada proses manajemen insiden. Hasil penelitian ini memberikan beberapa rekomendasi perbaikan terkait area-area insiden manajemen. Hasil pengukuran menggunakan maturity level yang ada pada COBIT 4.1, menunjukkan tingkat kematangan saat ini berada pada level 2 (Repeatable but Intuitive), dan melalui penggunaan Goal Question Metric, dimana terdapat 4 area yang perlu dilakukan perbaikan untuk membuat dokumen tata laksana manajemen, yaitu: penerapan helpdesk, penerapan SOP (Standard Operating Procedure), penerapan SLA (Service Level Agreement), dan penerapan team servicedesk.Kata kunci: Manajemen Insiden, IT Infrastucture Library, Tata Laksana